ANALISIS PROFESIONALISME GURU BERBASIS AGAMA, FILSAFAT, PSIKOLOGI DAN SOSIOLOGI PENDIDIKAN - Lisnawati Lisnawati; Ike Kurniati; Nandang Koswara; Faiz Karim Fatkullah (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2022)
The purpose of this study is to determine the professionalism of teachers as educators in order to improve the quality of education along with efforts to increase professionalism based on religion, philosophy, psychology, and sociology. This study uses qualitative research methods based on literature review or library research. The results of this study are : (1) Being an exemplary and professional teacher, must be based on the hadiths of the Prophet Muhammad and in sync with the Qur'an; (2) The philosophy of idealism is very important in education because at this stage, teachers must be able to bring out all the potential in students, both rationally and realistically; (3) Educational psychology as a tool for teachers to control themselves, and also provide learning assistance to students; (4) The role of the teacher in the perspective of the sociology of education can invite and direct the behaviour of students to actively socialize and communicate.